Development and evaluation of an animal-borne sensor prototype with integrated kinetic energy harvesting for rhinoceros conservation - Robinson, Simon (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.